2011
DOI: 10.1097/aud.0b013e31822229bd
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus in the General Population With a Focus on Noise and Stress: A Public Health Study

Abstract: Stress management strategies should be included in hearing conservation programs, especially for individuals with mild tinnitus who report a high stress load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 10 publications
6
54
1
5
Order By: Relevance
“…[8,9] The studies show that the odds ratio of tinnitus is raised by about 3%, with each year of age and that there is a higher risk of tinnitus for men compared with women. [10] Although tinnitus is a very common symptom, just a few risk factors related to behavior and habits have been proved.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] The studies show that the odds ratio of tinnitus is raised by about 3%, with each year of age and that there is a higher risk of tinnitus for men compared with women. [10] Although tinnitus is a very common symptom, just a few risk factors related to behavior and habits have been proved.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reviewed over 2,000 tinnitus patients and concluded that while exposure to both noise and stress were important for the probability and level of tinnitus discomfort, stress was the more important factor in determining whether a patient would transition from being mild or severely impacted. [24] It has also been reported that long-term stress and coping strategies were the strongest predictors of tinnitus, even stronger than traditional risk factors such as hearing loss, age, gender, and hyperacusis. [25] The use of music for setting and altering moods, arousing, and relaxing, is certainly not new.…”
Section: Introductionmentioning
confidence: 99%
“…Second, tinnitus can be classified along several dimensions which are worthwhile to consider (such as severity, duration, and etiology) [52] but were not covered in our study. It is reassuring though that most epidemiological studies used a comparable assessment of tinnitus like this study (e.g., [3,4,6,22,25]). Third, noise exposure could only be taken into account by a proxy measure in our study (i.e., occupation in office, laboratory, or production), yet evidence indicates that the association of stress with tinnitus is independent of actual external noise exposure [3].…”
Section: Discussionmentioning
confidence: 93%
“…Studies have demonstrated associations between psychological distress and tinnitus [3][4][5]. To the best of our knowledge, the current evidence on the role of work stress is restricted to only two studies [4,6].…”
Section: Introductionmentioning
confidence: 91%